The presence of single-nucleotide polymorphisms in hps4 gene in a subset of schizophrenic patients in Pahang: a preliminary study - Zainuddin, Norafiza; Mamat, Maizatul Akma; A. Talib, Norlelawati (International Islamic University Malaysia, 2017)
Schizophrenia is a devastating mental disorder that affects people’s normal life with heterogeneous features of its clinical presentation, as well as its molecular attribute. In order to identify the potential molecular aberration, particularly single nucleotide polymorphism (SNP) which could be important in the aetiology of schizophrenia, polymerase chain reaction (PCR)-DNA sequencing approach was utilized for targeting the exon (and intron) 9 of the Hermansky-Pudlak syndrome type 4 (HPS4) gene. DNAs were extracted from peripheral blood of nine schizophrenic patients and one normal individual prior to PCR-DNA sequencing. Following DNA sequencing, a SNP (A>G) which is rs713998 at nucleotide position 22618 of exon 9 of the HPS4 gene was observed in eight schizophrenia samples. Moreover, DNA sequencing results also revealed an intronic aberration/SNP which is rs3747129 (C>T) at nucleotide position 22789 of intron 9 of the HPS4 gene in four schizophrenia samples. A SNP which is rs739289 (G>T) at nucleotide position 22677 of the intron was also found in eight schizophrenia samples. The importance of both the exonic and intronic aberrations is yet to be confirmed with further research involving larger population and other relevant clinical parameters. That notwithstanding, these preliminary results suggested that single nucleotide aberrations, particularly SNPs might have a role in the development of schizophrenia.